The Antibacterial Activity of Thermoactinomyces sp. (H24) Extract Against Escherichia coli and Staphylococcus aureus - Julia Nanda Puspita; Rikhsan Kurniatuhadi; Rahmawati Rahmawati (Universitas Nahdlatul Ulama Surabaya, 2021)
Bacteria of the genus Thermoactinomyces have the ability to produce antibacterial bioactive compounds. This bioactive compound can be used for combating diarrheal agents such as Escherichia coli and Staphylococcus aureus. This study aims to determine the antibacterial activity of the metabolite extract from Thermoactinomyces sp. (H24) against Escherichia coli and Staphylococcus aureus. Methanol was used as a solvent for the extraction of bacterial bioactive compounds. Antibacterial activity was analyzed by the diffusion method with several extract concentrations (0.75 mL, 1.5 mL, 2.25 mL, and 3 mL), 10% DMSO as the negative control, and ciprofloxacin as the positive control. Our result shows that Termoactinomyces sp. (H24) extract has an inhibitory effect on the growth of E. coli and S. aureus with an effective concentration of 2.25 mL (inhibition strength: very strong).